Understanding Solid Waste Collectors’ Awareness of Occupational Hazards and Personal Protective Equipment Practices in Northern Malawi - Mercy Ngwira; Moses MN Chitete; Mary Sibande; Yoram Ngwira; Chitsanzo Damazio (Environmental Health Insights)
The purpose of this study was to evaluate Solid Waste Collectors’ (SWCs) knowledge of occupational hazards, their views on personal protective equipment (PPE), strategies for PPE use, and challenges in managing occupational risks. Previous studies have highlighted the importance of protective measures in addressing occupational hazards, but there was a need for further research to assess the knowledge levels of waste collectors regarding these hazards and PPE practices. This study used a qualitative research technique, specifically a phenomenological research design, to capture the lived experiences of SWCs. Focus group discussions and in-depth interviews were employed to gather data. Subgroups of topics were created by coding the data using a predefined codebook as part of the content analysis process. The findings revealed that SWCs are aware of the risks they face in their work environments. These risks range from longterm health issues caused by repeated exposure to harmful substances and injuries from sharp objects. However, a significant issue identified was the lack of accessibility and availability of PPE, which exposes waste collectors to various diseases and accidents and forces them to work without necessary safeguards. Efforts to increase PPE availability through public-private partnerships (PPPs) should be promoted. The city council should provide regular on-the-job training on health risks, occupational hazards related to waste collection, and PPE usage. Additionally, efficient channels for SWCs to report problems should be established to ensure their grievances are properly addressed.